Adapting the CROPGRO‐faba bean model to simulate the growth and development of Amaranthus species. (10th June 2022) - Nkebiwe, Peteh Mehdi; Boote, Ken; Pflugfelder, Annegret; Munz, Sebastian; Graeff‐Hönninger, Simone
Abstract: The aim of this study was to adapt the CROPGRO model to simulate growth and development processes of Amaranthus spp. under central European conditions. In 2017 and 2018, two field experiments with two amaranth cultivars (grain type, A. hypochondriacus L. Neuer Typ [NT]; fodder type, A. caudatus L. K63 [K63]) were conducted in southern Germany. Based on experimental and literature data, parameter coefficients that drive physiological processes at species, cultivar, and ecotype levels were calibrated to predict the time series experimental observations of various growth and development traits. Statistical evaluation of the model adaptation was performed using root mean square error (RMSE, in variable units, 0 equals perfect fit) and the Willmott agreement index (d‐Stat., range from 0 to 1, 1 equals perfect fit). For NT and K63, respectively, the model adaptation led to accurate predictions of canopy height (RMSE, 0.07 and 0.24 m; d‐Stat., 0.98 and 0.92), panicle weight (RMSE, 2, 034 and 1, 153 kg ha –1 ; d‐Stat., 0.92 and 0.94), panicle harvest index (RMSE, 0.05 and 0.06; d‐Stat., 0.99 and 0.96), leaf N concentration (RMSE, 0.38 and 0.40%; d‐Stat., 0.94 and 0.92) and aboveground biomass (RMSE, 2, 948 and 2, 572 kg ha –1 ; d‐Stat., 0.88 and 0.91). In summary, the CROPGRO model was successfully adapted for Amaranthus spp. The adapted model can be further improved as it is made available for evaluation in different locations and environments including limited soil N supply. Core Ideas: A physiological process‐based mechanistic model was adapted to Amaranthus ssp. for the first time. Panicle weight and harvest index, leaf N concentration, and aboveground biomass were accurately predicted. Amaranth showed a low requirement for N and considerable drought tolerance.